2017
DOI: 10.1002/ajmg.a.38066
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous mutation in PRUNE1 in an Oji‐Cree male with a complex neurological phenotype

Abstract: The PRUNE1 gene encodes a member of the phosphoesterases (DHH) protein superfamily that is highly expressed in the human fetal brain and involved in the regulation of cell migration. Homozygous or compound heterozygous PRUNE1 mutations were recently identified in five individuals with brain malformations from four families. We present a case of a 2-year-old male with a complex neurological phenotype and abnormalities on brain MRI. Re-annotation of clinical whole-exome sequencing data revealed a homozygous like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…Eight mutations in PRUNE1 (7 coding mutations: p.Asp30Asn, p.Pro54Thr, p.Asp106Asn, p.Arg128Gln, p.Gly174*, p.His292Glnfs*3 and p.Arg297Trp, and one splicing mutation: c.521‐2A>G) have been reported . PRUNE1 forms a homodimer via the C‐terminal cortexillin homology (CHD) domain .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight mutations in PRUNE1 (7 coding mutations: p.Asp30Asn, p.Pro54Thr, p.Asp106Asn, p.Arg128Gln, p.Gly174*, p.His292Glnfs*3 and p.Arg297Trp, and one splicing mutation: c.521‐2A>G) have been reported . PRUNE1 forms a homodimer via the C‐terminal cortexillin homology (CHD) domain .…”
Section: Discussionmentioning
confidence: 99%
“…To date, 8 germline mutations have been identified from 23 affected individuals in 13 families: p.Asp30Asn, p.Pro54Thr, p.Asp106Asn, p.Arg128Gln, p.Gly174*, p.His292Glnfs*3, p.Arg297Trp and c.521‐2A>G. Common major features of biallelic PRUNE1 mutations include global developmental delay, intellectual disability, progressive microcephaly, plagiocephaly, hypotonia, spastic quadriparesis, hyperreflexia, seizures, limb contractures, optic features (congenital cataract and optic atrophy) and abnormal brain magnetic resonance imaging (MRI) (cerebral and cerebellar atrophy, delayed myelination, thin corpus callosum and white matter abnormalities) . Patients are from various backgrounds: Saudi Arabia, Turkey, United States, Oman, Iran, Italy, India and Ojibwe‐Cree . Here, we describe 1 reported and 2 novel PRUNE1 mutations and atypical clinical manifestations in 1 Caucasian and 3 Japanese families.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-genome sequencing (WGS) has the potential to revolutionize our approach to clinical genetic diagnostics [1][2][3][4][5]. One proposed advantage of whole-exome sequencing (WES) and WGS is the opportunity for periodic reanalysis of the data in individuals not diagnosed on initial testing [2,[6][7][8][9][10]. The Genome Clinic at The Hospital for Sick Children (Toronto, Canada) is a longitudinal multifaceted research project designed to integrate WGS into mainstream clinical practice [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we performed detailed literature and clinical review of all 35 NMIHBA patients reported to date in order to better understand the phenotypic spectrum of NMIHBA (Table 1, Figure 1) (8)(9)(10)(11)(18)(19)(20) suggesting peripheral neuropathy as part of the clinical spectrum of NMIHBA (18). Other patients also showed neurogenic findings on electromyography (EMG) studies and spinal motor neuron involvement.…”
Section: Clinical Description Of Nmihba Patientsmentioning
confidence: 99%
“…Additionally, we performed detailed literature and clinical review of all 35 NMIHBA patients reported to date in order to better understand the phenotypic spectrum of NMIHBA (Table 1,Figure 1)(8)(9)(10)(11)(18)(19)(20). Consistent features across the majority of patients include severe global developmental delay (94.59%), profound intellectual disability (91.89%) with absent language (83.78%) and brain abnormalities (86.48%) characterized primarily by cerebral and cerebellar atrophy, thin corpus callosum, and white matter changes.…”
mentioning
confidence: 99%